Coarse-grained modelling of triglyceride crystallisation: a molecular insight into tripalmitin tristearin binary mixtures by molecular dynamics simulations. (16th November 2015) - Pizzirusso, Antonio; Brasiello, Antonio; De Nicola, Antonio; Marangoni, Alejandro G; Milano, Giuseppe
Abstract: The first simulation study of the crystallisation of a binary mixture of triglycerides using molecular dynamics simulations is reported. Coarse-grained models of tristearin (SSS) and tripalmitin (PPP) molecules have been considered. The models have been preliminarily tested in the crystallisation of pure SSS and PPP systems. Two different quenching procedures have been tested and their performances have been analysed. The structures obtained from the crystallisation procedures show a high orientation order and a high content of molecules in the tuning fork conformation, comparable with the crystalline α phase. The behaviour of melting temperatures for the α phase of the mixture SSS/PPP obtained from the simulations is in qualitative agreement with the behaviour that was experimentally determined.